2012
DOI: 10.1007/s11033-012-1838-y
|View full text |Cite
|
Sign up to set email alerts
|

Fatty acid synthase expression and esophageal cancer

Abstract: Fatty acid synthase (FASN) overexpression has also been associated with a variety of human malignancies including tumor progression, aggressiveness, and metastasis. To investigate the role of FASN expression in esophageal cancer, we evaluated 60 cases of squamous cell carcinoma, 20 cases of adenocarcinoma, and 10 cases of normal esophageal tissues. We found that FASN was detected in 95 % human squamous cell carcinoma, and in 90 % human adenocarcinoma samples. However, all cases of normal esophageal epithelium … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
26
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 14 publications
0
26
0
Order By: Relevance
“…Both FAS and SCD1 activities support cancer cell growth and survival, as it was found in breast and endometrial cancer [25]. It was suggested that the FAS expression is of functional importance in human esophageal tumorigenesis, and that inhibiting FAS might be applied to treat esophageal cancer [26]. …”
Section: Discussionmentioning
confidence: 99%
“…Both FAS and SCD1 activities support cancer cell growth and survival, as it was found in breast and endometrial cancer [25]. It was suggested that the FAS expression is of functional importance in human esophageal tumorigenesis, and that inhibiting FAS might be applied to treat esophageal cancer [26]. …”
Section: Discussionmentioning
confidence: 99%
“…The expression of FASN is relatively low in normal tissue since fatty acid is generally supplied by diet, but aberrantly elevated in various types of cancer including breast, prostate, colon, ovarian, and esophageal carcinomas (7)(8)(9)(10). Interestingly, de novo synthesized fatty acids regulate glucose, lipid, and cholesterol metabolism through activation of PPAR␣ in adult liver (11).…”
mentioning
confidence: 99%
“…FASN is often highly expressed in human cancer, whereas it is usually undetectable or exhibits low expression in the majority of normal human tissues (13)(14)(15)(16)(17). This differential tissue distribution makes FASN an attractive target for the development of novel anticancer techniques (13)(14)(15)(16). Zhou et al evaluated 80 samples of esophageal cancer, revealing that FASN is primarily localized in the cytoplasm of esophageal cancer, but exhibited little or no expression in normal esophageal tissues (16).…”
Section: Discussionmentioning
confidence: 99%
“…This differential tissue distribution makes FASN an attractive target for the development of novel anticancer techniques (13)(14)(15)(16). Zhou et al evaluated 80 samples of esophageal cancer, revealing that FASN is primarily localized in the cytoplasm of esophageal cancer, but exhibited little or no expression in normal esophageal tissues (16). Similarly, Kao et al (15) investigated FASN expression in nasopharyngeal carcinoma using immunohistochemistry and revealed that FASN was positively expressed in the tumoral cytoplasm, but exhibited low or no expression in non-tumor epithelium.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation